Syntheses of doubly linked proanthocyanidins using free flavan units as nucleophiles: insight into the origin of the high regioselectivity of annulation. Issue 41 (4th October 2019) - Betkekar, Vipul V.; Harachi, Mio; Suzuki, Keisuke; Ohmori, Ken
Abstract : Reported herein is a viable synthesis route to procyanidins A1 and A2, doubly linked flavan dimers. The use of nascent nucleophilic partner, catechin or epicatechin, enabled facile regioselective annulation with an ethylenedioxy-bridged flavan unit. Abstract : A synthesis method of doubly linked flavan dimers is reported via the acid-promoted annulation reaction using nascent catechins, (+)-catechin or (−)-epicatechin, as a dianionic partner and an ethylenedioxy-bridged flavan as a dicationic partner. Procyanidins A1 and A2 were synthesized. On the high regioselectivity of the annulation reactions, model experiments and computational studies were carried out.